THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE ON TEACHER PERFORMANCE THROUGH JOB SATISFACTION AT SMA NEGERI 1 NABIRE - Marthen Madai; I Nengah Suarmanayasa; Komang Krisna Heryanda (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the effect of transformational leadership and organizational culture on teacher performance through job satisfaction at SMA Negeri 1 Nabire. The research employed a quantitative approach with an associative research design. The population consisted of all teachers at SMA Negeri 1 Nabire totaling 56 respondents, who were also used as the research sample. Data were collected through a questionnaire using a Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results indicate that transformational leadership has a positive and significant effect on both job satisfaction and teacher performance, while organizational culture has a positive and significant effect on job satisfaction but does not directly affect teacher performance. Job satisfaction is found to have a positive and significant effect on teacher performance and acts as a mediating variable in the research model. Job satisfaction partially mediates the relationship between transformational leadership and teacher performance and fully mediates the relationship between organizational culture and teacher performance. These findings suggest that improving teacher performance is influenced not only by leadership and organizational culture but also by the level of teachers’ job satisfaction. Therefore, strengthening transformational leadership and fostering an organizational culture that enhances teachers’ job satisfaction are important strategies for improving teacher performance, particularly in schools located in areas with limited resources.